A Rab11a-Rab8a-Myo5B network promotes stretch-regulated exocytosis in bladder umbrella cells - Khandelwal, Puneet (The American Society for Cell Biology, 2013)
Multiple Rabs are associated with secretory granules/vesicles, but how these GTPases are coordinated to promote regulated exocytosis is not well understood. In bladder umbrella cells a subapical pool of discoidal/fusiform-shaped vesicles (DFVs) undergoes Rab11a-dependent regulated exocytosis in response to bladder filling. We show that Rab11a-associated vesicles are enmeshed in an apical cytokeratin meshwork and that Rab11a likely acts upstream of Rab8a to promote exocytosis. Surprisingly, expression of Rabin8, a previously described Rab11a effector and guanine nucleotide exchange factor for Rab8, stimulates stretch-induced exocytosis in a manner that is independent of its catalytic activity. Additional studies demonstrate that the unconventional motor protein myosin5B motor (Myo5B) works in association with the Rab8a–Rab11a module to promote exocytosis, possibly by ensuring transit of DFVs through a subapical, cortical actin cytoskeleton before fusion. Our results indicate that Rab11a, Rab8a, and Myo5B function as part of a network to promote stretch-induced exocytosis, and we predict that similarly organized Rab networks will be common to other regulated secretory pathways.